Evaluation of drought tolerance of soybean on antioxidant enzymes and aldehyde (Experimental biology, 2016)
The aim of this study was to investigate the expression of antioxidant enzymes - peroxidase (POD) and superoxide dismutase (SOD), aldehyde oxidase (AO) at the level of enzyme activity in order to increase the efficiency of breeding drought-tolerant soybean genotypes.We have studied the cultivated soybean Glycine max L. of the world collection according to the preliminary data having signs of drought resistance: vr. Ustya (Ukraine), K589109 (Russia), K583583 HMAS 84 (USA) and related to early maturing group with vegetation period of 85-95 days. The standard used was variety of domestic breeding - Almaty.Determination of the enzymatic activity of SOD, POD and AO in the leaves of soybean was conducted under irrigation and drought in two reproductive phases of vegetation, the most sensitive to moisture deficit - in the flowering stage R1 and bean filling R5.Screening of the enzymatic activity of SOD, POD and AO showed the distinct correlation links between activity and drought tolerance in Almaty (Kazakhstan) and K583583 (USA) varieties.
Keywords: drought resistance indices; reactive oxygen species; antioxidant enzymes; aldehyde oxidase.